Tachysurus spilotus, a new species of catfish from central Vietnam (Teleostei: Bagridae) - Ng, Heok Hee (Zootaxa, 2009)
Tachysurus spilotus, a new species of catfish from central Vietnam, is described. It can be distinguished from congeners except T. argentivittatus, T. longispinalis, and T. virgatus in having a color pattern consisting of black longitudinal stripes on a pale body (vs. with a uniform-colored body with pale patches or transverse bands on a dark body, or with dark rectangular patches on a pale body). It differs from both T. argentivittatus and T. virgatus in snout shape and having gently convex (vs. straight) posterior edges of the caudal-fin lobes; and from T. longispinalis in having a shorter dorsalfin spine (ca. 27% SL vs. 15.1–19.0) and maxillary barbels (shorter, vs. longer than head). Tachysurus mica is shown here to be conspecific with—and a junior synonym of—T. argentivittatus.